Pheochromocytoma in Congenital Cyanotic Heart Disease - Carmen Aresta; Gianfranco Butera; Antonietta Tufano; Giorgia Grassi; Livio Luzi; Stefano Benedini (Case Reports in Endocrinology)
Studies on genome-wide transcription patterns have shown that many genetic alterations implicated in pheochromocytoma-paraganglioma (P-PGL) syndromes cluster in a common cellular pathway leading to aberrant activation of molecular response to hypoxia in normoxic conditions (the pseudohypoxia hypothesis). Several cases of P-PGL have been reported in patients with cyanotic congenital heart disease (CCHD). Patients affected with CCHD have an increased likelihood of P-PGL compared to those affected with noncyanotic congenital heart disease. One widely supported hypothesis is that chronic hypoxia represents the determining factor supporting this increased risk. We report the case of a 23-year-old woman affected with congenital tricuspid atresia surgically by the Fontan procedure. The patient was admitted to hospital with hypertensive crisis and dyspnea. Chest computed tomography revealed, incidentally, a 6-cm mass in the left adrenal lodge. Increased levels of noradrenaline (NA) and its metabolites were detected (plasma NA 5003.7 pg/ml, n.v.<480; urinary NA 1059.5 µg/24 h, n.v.<85.5; urinary metanephrine 489 µg/24 h, n.v.<320). The patient did not report any additional symptom related to catecholamine excess. The left adrenal tumor showed abnormal accumulation when 131I-metaiodobenzylguanidine scintigraphy was performed. A 18F-fluorodeoxyglucose positron emission tomography showed no significant metabolic activity in the left adrenal gland but intense uptake in the supra- and subdiaphragmatic brown adipose tissue, probably due to noradrenergic-stimulated glucose uptake. The patient underwent left open adrenalectomy after preconditioning with α- and β-blockers and histopathological examination confirmed the diagnosis of pheochromocytoma (Ki-67<5%). Screening for germline mutations did not show any genes mutation (investigated mutations: RET, TMEM127, MAX, SDHD, SDHC, SDHB, SDHAF2, SDHA, and VHL). Clinicians should consider P-PGL when an unexplained clinical deterioration occurs in CCHD patients, even in the absence of typical paroxysmal symptoms.